Fundamentos filosóficos e antropológicos da..Fundamentos filosóficos y antropológicos de la teoría del Sich-bewegen y la formación de sujetos emancipados, autónomos y críticos: El ejemplo del currículo de educación física en el estado de São Paulo - Betti, Mauro [UNESP]; Knijnik, Jorge; Venâncio, Luciana [UNESP]; Neto, Luiz Sanches [UNESP]; Daolio, Jocimar (My University, 2014)
This article examines philosophical and anthropological underpinnings of the Sich-Bewegen Theory, based on the phenomenological philosophy by Merleau-Ponty and social anthropology by Mauss and Geertz. It also considers implications for Physical Education Elementary and High School curricula aimed at forming emancipated, autonomous and critical individuals, taking the Physical Education Curriculum of the State of São Paulo as example. It concludes that the curriculum needs to imbricate into students’ social life and take into account the challenges and issues from contemporary society.
Fundamentos filosóficos e antropológicos da teoria do se-movimentar e a formação de sujeitos emancipados, autônomos e críticos: O exemplo do currículo de educação física do estado de São Paulo
Philosophical and anthropological foundations of sich-bewegen theory and the formation of emancipated, autonomous and critical subjects: The example of physical education curriculum in the State of São Paulo
Keywords: Curriculum; Human movement; Phenomenology; Social anthropology